1988
DOI: 10.1111/j.1600-0714.1988.tb01539.x
|View full text |Cite
|
Sign up to set email alerts
|

The proportion of suppressor‐inducer T‐lymphocytes is reduced in recurrent aphthous stomatitis

Abstract: Savage NW, Mahanonda R, Seymour GJ, Bryson GJ, Collins RJ. The proportion of suppressor-inducer T-lymphoeytes is reduced in recurrent aphthous stomatitis. J Oral Pathol 1988: 17: 293-297. A flow cytometric analysis of peripheral blood lymphocytes was undertaken in recurrent aphthous stomatitis patients. The project aimed at detecting differences within lymphocyte subsets using type-specific monoclonal antibodies. Peripheral blood samples were taken from RAS patients in both active and remission phases of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…No viruses have been directly isolated from RAS lesions or found using cytology or electron microscopy. However, the increased CD8+ count and the decreased CD4 count during active RAS (26) may, at least partially, support a possible viral etiology, as discussed elsewhere (27).…”
Section: Predisposing Factorsmentioning
confidence: 74%
“…No viruses have been directly isolated from RAS lesions or found using cytology or electron microscopy. However, the increased CD8+ count and the decreased CD4 count during active RAS (26) may, at least partially, support a possible viral etiology, as discussed elsewhere (27).…”
Section: Predisposing Factorsmentioning
confidence: 74%
“…Although several etiological factors have been proposed, the exact cause underlying RAS remains unclear . Previous investigations have demonstrated alterations of T lymphocytes subsets in RAS patients . Immunohistochemical studies have shown an increased number of CD4+ lymphocytes in the pre‐ulcerative oral aphthous lesions and a predominance of CD8+ lymphocytes in the ulcerative oral aphthous lesions .…”
Section: Introductionmentioning
confidence: 99%
“…These alterations mainly regard T CD4+ lymphocytes, in fact it was possible to observe a substantial reduction of "naivesuppressor" CD4+CD45RA+ lymphocytes and an increase of the "memory-helper" CD4+CD45RO+ CD29+ subpopulation in all patients studied. Some Authors found similar alterations in other diseases like Aphthous Recurrent Stomatitis (25), Systemic Lupus Erythematosus (SLE) (26), Multiple Sclerosis (MS) (27). However, depression of the "suppressor" activity could be a consequence rather than a cause of these diseases.…”
Section: Tab II Distribution Of Lymphocyte Subpopulation In Olp Pa mentioning
confidence: 94%